Endomorphisms of some ordered semi-groups - Gabovich, E. (Lithuanian Mathematical Journal, 1963)
The abstracts (in two languages) can be found in the pdf file of the article.Original author name(s) and title in Russian and Lithuanian:Е. Габович. Эндоморфизмы некоторых упорядоченных полугруппE. Gabovičius. Kai kurių sutvarkytų pusgrupių endomorfizmai